Analisa Perbandingan Atas Undang Undang Pemerintahan Daerah Di Indonesia - Setiawan, Wawan Dharma (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2010)
Implementation of Local governance as a mandate from the Constitution since the early days of independence has been attempted, but until these days, central government still has more power than local governments. Apparently the local governmentarea was not ready and not prepared to alter the delivery of local governance pendulum that is on decentralization as a manifestation of regional autonomy. In order to resolve this negative euphoria, those transfers of powers should be done by a process that is systematic, measurable